Brahms, Autodidacticism, and the Curious Case of the Gavotte - Ennis, Martin (Current Musicology, 2019)
In later decades, Johannes Brahms repeatedly stressed the inadequacy of his musical education, claiming he learned nothing from Eduard Marxsen and Robert Schumann, the two figures usually regarded as his principal mentors. In this article, a tribute to the Brahms scholar Robert Pascall who died in June 2018, I test the reliability of Brahms’s comments, concluding that he enjoyed a thorough training; in fact, Marxsen emerges from the study as a remarkably effective pedagogue. Nonetheless, after leaving Hamburg in 1853 Brahms embarked on an autodidactic program probably without parallel in nineteenth-century Germany. This program, based largely on the exploration of Baroque scores and treatises, was a course of study he would later encourage aspirant composers to replicate. The article views Brahms’s autodidacticism through the lens of meter, with a focus on compositions that reference the gavotte, a particularly pertinent genre given that its metrical layout was often confused. I reveal that Brahms’s practice in compositions related to the gavotte sometimes contradicts advice he offered friends and pupils; it also sits uncomfortably alongside the composer’s response to the rebarrings of musical classics advocated by Hugo Riemann. These various inconsistencies encourage us to look afresh at the agenda that lay behind Brahms’s stance on pedagogy and learning. I argue in conclusion that Brahms used his own musical education as a form of self-justification in ongoing disputes with the New German School.